Exploring the Impact of Temperature and Solvent Ratio on Phenol and Flavonoid Levels in Alpinia galangal L. Extract Using Evaporative Vacuum Cooling - Dina Wahyu Indriani; Firdha Dwi Anggraini; Yusuf Hendrawan; Anang Lastriyanto (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
The objective of this research is to determine the impact of temperature gradients and solvent ratios in the evaporative vacuum cooling method on the yield of phenol and flavonoid content in galangal extract; ascertain the impact of these factors on the yield generated by galangal extract; and ascertain the mass balance analysis of materials are the objectives of this study. Throughout the extraction of galangal. The study's findings demonstrated that the evaporative vacuum cooling technique, conducted at 49 ºC and with a 1:1 solvent ratio of 1.4432±0.7317 mg GAE/g, produced the highest total phenol concentration. The three differences in the temperature of the evaporative vacuum produced the total phenol content cooling. The overall phenol content obtained decreases with increasing solvent ratio addition. Although the evaporative vacuum cooling treatment at 45 °C yielded the highest total flavonoid content (1.2418±0.2365 mg QE/g) at a 1:2 solvent ratio, the total flavonoid content varied between the three evaporative vacuum cooling temperature variations. The yield of total phenolic and flavonoid compounds was not significantly affected by temperature gradient adjustments or the ratio of galangal extract to solvent (Sig. > 0.05) in any of the data samples pertaining to phenolic and flavonoid compounds. Keywords: Evaporative vacuum cooling, Flavonoids, Galangal, Phenol.